Planning and production control in mining operations - De la Cruz Carrasco, Estanislao (1999)
The planning and control of production in operation of the mining area is applied to achieve the goals or objectives, which are drawn up in a production unit of a mining company and this will depend on the type of organization that the company has. The production unit at medium mining level, has the following departments: geology, mines, concentrator, maintenance, security, logistics, medical, industrial relations, accounting, engineering and training. Of which all have to program their annual, quarterly and monthly plan. The head of the mining department, who is the general head of mines, together with his section heads will plan the daily and monthly production according to the capacity of the treatment plant and in coordination with all the departments. The concentrator department will plan the production of concentrates based on the head grade, the grade that the concentrates to be obtained will have, the volume of the tailings with their respective grades. The maintenance department plans that all of its mine equipment and machinery, concentrator are operational with a minimum of 75% availability, to ensure compliance with the objectives that the aforementioned departments have set. The head of the security department or security program also called (security, health and environment), schedules the different activities that will be carried out jointly with operations and the different departments of the production unit, which consist of inspections, talks , meetings with supervisors and with the central safety committee, to analyze the accidents of the month or other problems or events that occurred in the unit. Then, it will be implemented, the development of which will be controlled day by day in accordance with the control chart that each department has. This is done in the morning meetings (staff meeting) in which only the heads of mine, plant, maintenance and security participate, and the production meetings, with the participation of the different department heads with their respective section heads chaired by the unit superintendent. According to the fulfillment of programs of the different departments, we will have the result of the production unit of the company.